Perovskite crystal combination material, solar cell, laminated cell and photovoltaic module
By using organic additives with specific structures in perovskite solar cells, the passivation effect is achieved, and the problem that traditional additives cannot improve photoelectric conversion efficiency and long-term stability is solved, and an efficient and stable perovskite solar cell is achieved.
Patent Information
- Application Number
- CN202411439777.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional organic additives cannot improve the photoelectric conversion efficiency of perovskite solar cells while improving their long-term stability in the working environment, limiting the industrial application of perovskite solar cells.
Provided is a perovskite crystallization combination material, including a perovskite precursor and an organic additive having a specific structure coordinated by a breaking bond between the lonely pair of electrons of oxygen atoms in an ester group and a metal bond at the grain boundary or interface, And hydrogen bonds are formed by breaking the bond between the ester group and the halogen to achieve dual chemical passivation effect.
It effectively reduces non-radiative recombination at grain boundaries or interfaces, improves the mechanical durability and filling factor of the perovskite layer, and achieves high photoelectric conversion efficiency and excellent long-term stability.
Smart Images

Figure CN119421628A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a perovskite crystal combination material, a solar cell, a stacked cell and a photovoltaic module. Background Art
[0002] Perovskite Solar Cells (PSCs) are devices that use perovskite-type organic metal halide semiconductors as light-absorbing materials to directly convert light energy into electrical energy through the photovoltaic effect. Various device engineering strategies have promoted the commercialization of high-performance perovskite solar cells, such as additive engineering and surface passivation engineering. However, perovskite solar cells will experience extreme conditions such as rain, high and low temperatures, and ultraviolet radiation during long-term outdoor operation, leading to a series of problems such as battery failure and lead leakage.
[0003] In order to solve the biggest challenges in the commercialization of perovskite solar cells, including the long-term stability of the cells and the environmental pollution caused by lead leakage, the development of suitable organic additives is an important solution. However, traditional organic additives cannot improve the long-term stability of perovskite solar cells in the working environment while improving the photoelectric conversion efficiency of perovskite solar cells, which limits the industrial application of perovskite solar cells. Summary of the invention
[0004] Based on this, it is necessary to provide a perovskite crystalline composite material, solar cell, stacked cell and photovoltaic module to overcome the problem that traditional organic additives cannot improve the photoelectric conversion efficiency of perovskite solar cells while improving their long-term stability in the working environment.
[0005] In a first aspect of the present application, a perovskite crystalline composite material is provided, comprising a perovskite precursor and an organic additive;
[0006] The organic additive has a structure as shown in the general formula (I):
[0007] (I);
[0008] Each occurrence of R1 independently includes -H and a substituted or unsubstituted C1~C6 alkyl group;
[0009] R2 includes one of a substituted or unsubstituted C1~C6 alkylene group and a substituted or unsubstituted C1~C6 alkyleneoxy group.
[0010] In one embodiment, each occurrence of R1 independently includes one of -H and C1~C3 alkyl;
[0011] R2 includes one of C2~C4 alkylene, halogen-substituted C4~C6 alkylene, amino-substituted C4~C6 alkylene and C2~C4 alkyleneoxy.
[0012] In one embodiment, each occurrence of R1 independently comprises one of -H and -CH3;
[0013] R2 includes -CH2CH2-, -CH2OCH2-, -CH2(CF2)4CH2- and One of the following, wherein * represents a connection site.
[0014] In one embodiment, the molar ratio of the perovskite precursor to the organic additive is 1:(0.005~0.3).
[0015] In one embodiment, the perovskite crystalline composite material further includes a perovskite additive and an organic solvent.
[0016] In one embodiment, the chemical formula of the perovskite precursor is ABX3, wherein the A ions include FA + 、MA + , Cs + , Rb + and K + One or more of the B ions include Pb 2+ Sn 2+ and Ge 2+ One or more of the following, X ions include Cl - Br - ,I - , CN - and SCN - One or more of .
[0017] In one embodiment, the perovskite additive includes one or more of MACl, PbCl2, MABr, FAI and halogen ammonium salts.
[0018] In one embodiment, the molar ratio of the perovskite precursor to the perovskite additive is 1:(0.005~0.3).
[0019] In one embodiment, the organic solvent includes one or more of N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, dimethyl sulfoxide, ethanol, isopropanol and acetone.
[0020] In a second aspect of the present application, a method for preparing a solar cell is provided, comprising the following steps:
[0021] forming a perovskite layer on a substrate layer using a perovskite crystal combination material;
[0022] The perovskite crystalline composite material is the perovskite crystalline composite material as described above.
[0023] In one embodiment, the perovskite precursor and the organic additive contained in the perovskite crystalline composite material are mixed, and the perovskite layer is formed on the substrate layer using the perovskite crystalline composite material, comprising the following steps:
[0024] preparing a mixed solution containing the perovskite precursor and the organic additive;
[0025] Applying the mixed solution on the base layer to form a first liquid film;
[0026] The first liquid film is annealed to prepare the perovskite layer.
[0027] In one embodiment, the perovskite precursor and the organic additive contained in the perovskite crystalline composite material are independent of each other, and forming a perovskite layer on a substrate layer using the perovskite crystalline composite material comprises the following steps:
[0028] preparing a first solution containing the perovskite precursor and a second solution containing the organic additive;
[0029] The first solution and the second solution are used to form adjacent perovskite layers and interface modification layers on the substrate layer using a solution method.
[0030] In one embodiment, forming a perovskite layer on a substrate layer using a perovskite crystalline combination material comprises the following steps:
[0031] preparing a third solution containing the perovskite precursor and a portion of the organic additive, and a fourth solution containing the remaining organic additive;
[0032] The third solution and the fourth solution are used to form adjacent perovskite layers and interface modification layers on the substrate layer using a solution method.
[0033] In a third aspect of the present application, a solar cell is provided, which is manufactured using the solar cell manufacturing method as described above.
[0034] In one embodiment, the solar cell comprises a first carrier transport layer, a perovskite layer, a second carrier transport layer and a top electrode which are stacked in sequence; or,
[0035] The solar cell comprises a first carrier transport layer, a perovskite layer, an interface modification layer, a second carrier transport layer and a top electrode which are stacked in sequence.
[0036] In a fourth aspect of the present application, a stacked cell is provided, comprising a silicon cell, a composite layer and a top cell stacked in sequence, and the top cell is the solar cell as described above.
[0037] In a fifth aspect of the present application, a photovoltaic module is provided, comprising a first packaging panel, a first packaging film, a battery string, a second packaging film and a second packaging panel stacked in sequence, and the battery string is formed by electrically connecting a plurality of solar cells as described above, or by electrically connecting a plurality of stacked batteries as described above.
[0038] This application has at least the following beneficial effects:
[0039] The organic additive contained in the perovskite crystal combination material of the present application has two acrylic functional groups, and the lone pair of electrons of the oxygen atom in the ester group coordinates with the metal bond break (such as lead bond break) at the grain boundary or interface, and the ester group forms a hydrogen bond with the halogen bond break, thereby achieving a dual chemical passivation effect, effectively reducing the non-radiative recombination at the grain boundary or interface. The organic additive has only two cross-linking sites, and will not form a cross-linked polymer with spatial stereoscopicity, but will form a cross-linked polymer with a flexible main chain, which is conducive to reducing the system hardness of the rigid perovskite material, and well fills the grain boundaries in the perovskite film, thereby improving the filling factor of the device. At the same time, the organic additive, as a macromonomer that can undergo cross-linking polymerization, overcomes the problems of high activity, volatility and easy diffusion and migration of organic small molecules, and improves the mechanical durability of the perovskite layer. In addition, the flexible regulation of R1 and R2 in the organic additive can play the role of water and oxygen blocking and adjusting the band gap. Therefore, the perovskite solar cell prepared by the perovskite crystal combination material provided by the present application not only achieves high photoelectric conversion efficiency, but also shows excellent long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0041] Figure 1 is a schematic structural diagram of a solar cell according to Example 1;
[0042] Figure 2 is a schematic structural diagram of a solar cell according to Example 2;
[0043] Figure 3 is a schematic structural diagram of a solar cell according to Example 3;
[0044] Figure 4A schematic diagram of the structure of a solar cell of Comparative Example 1;
[0045] Figure 5 This is a graph showing the MPPT stability test results of the solar cell of Example 3;
[0046] Figure 6 The stability comparison diagram of the solar cells of Examples 1 to 3 and Comparative Example 1 under different conditions;
[0047] Figure 7 JV curves of solar cells of Examples 1, 4 and 5;
[0048] Figure 8 JV curves of solar cells of Examples 2, 6 and 7;
[0049] Fig. 9 The JV curves of the solar cells of Examples 3, 8 and 9 are shown.
[0050] Figure numerals: transparent conductive layer 11, hole transport layer 12, perovskite layer 13, electron transport layer 14, top electrode 15; transparent conductive layer 21, hole transport layer 22, perovskite layer 23, interface modification layer 24, electron transport layer 25, top electrode 26; transparent conductive layer 31, hole transport layer 32, perovskite layer 33, interface modification layer 34, electron transport layer 35, top electrode 36; transparent conductive layer 41, hole transport layer 42, perovskite layer 43, electron transport layer 44, top electrode 45. DETAILED DESCRIPTION
[0051] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0053] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0054] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0055] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0056] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0057] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0058] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0059] the term
[0060] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0061] In the present application, when a substituent with the same symbol appears multiple times, each substituent may be the same or different from each other. For example, when a general formula contains multiple R, R may be the same or different from each other.
[0062] "Alkyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. Alkyl can represent a straight chain, branched and / or cyclic alkyl group. The carbon number of the alkyl group can be 1 to 50, 1 to 30, 1 to 20, 1 to 10 or 1 to 6. Phrases containing this term, for example, "C1 to C6 alkyl" refers to an alkyl group containing 1 to 6 carbon atoms, and each occurrence can be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl or C6 alkyl. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -C H(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl -1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl ( -CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3).
[0063] "Alkylene" refers to a hydrocarbon group with two monovalent radical centers derived from an alkyl group by removing a hydrogen atom, which can be a saturated branched alkyl group or a saturated straight-chain alkyl group. For example, "C1-C6 alkylene" means that the alkyl portion contains 1 to 6 carbon atoms, and each occurrence can be independently C1 alkylene, C2 alkylene, C3 alkylene, C4 alkylene, C5 alkylene or C6 alkylene. Suitable examples include, but are not limited to: methylene (-CH2-), 1,1-ethyl (-CH(CH3)-), 1,2-ethyl (-CH2CH2-), 1,1-propyl (-CH(CH2CH3)-), 1,2-propyl (-CH2CH(CH3)-), 1,3-propyl (-CH2CH2CH2-) and 1,4-butyl (-CH2CH2CH2CH2-).
[0064] "Alkoxy" refers to a group having -O-alkyl in which at least one carbon atom is replaced by an oxygen atom on the basis of an alkyl group. Phrases containing this term, for example, "C1~C6 alkoxy" means that the alkyl part contains 1 to 6 carbon atoms, and each occurrence can be independently C1 alkoxy, C2 alkoxy, C3 alkoxy, C4 alkoxy, C5 alkoxy or C6 alkoxy. Suitable examples include, but are not limited to: -O-CH3, -O-CH2CH3, -CH2-O-CH3, -CH2-O-CH2CH3 and -OC(CH3)3.
[0065] "Alkyleneoxy" is a group having -O-alkylene in which at least one carbon atom is replaced by an oxygen atom on the basis of an alkylene group. A phrase containing this term, for example, "C1~C6 alkyleneoxy" means that the alkylene part contains 1 to 6 carbon atoms, and each occurrence can be independently C1 alkyleneoxy, C2 alkyleneoxy, C3 alkyleneoxy, C4 alkyleneoxy, C5 alkyleneoxy or C6 alkyleneoxy. Suitable examples include, but are not limited to: -O-CH2-, -O-CH2CH2-, -O-CH(CH3)-, -CH2-O-CH2-, -CH2-O-CH2CH2-, -CH2-O-CH(CH3)-, -OC(CH3)2CH2-, and -CH2-OC(CH3)2-.
[0066] "Substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group may be substituted by one or more substituents acceptable in the art. Suitable substituents include but are not limited to: C1~C 20Alkyl, cycloalkyl containing 3 to 20 ring atoms, heterocyclic group containing 3 to 20 ring atoms, aryl containing 6 to 20 ring atoms, heteroaryl containing 5 to 20 ring atoms, silanyl, halogen, hydroxyl, amino, nitro, phosphate, boric acid, carboxyl, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, haloformyl, formyl, cyano, isocyano, isocyanate, thiocyanate, isothiocyanate or trifluoromethyl, and the above groups may also be further substituted by substituents acceptable in the art.
[0067] The "number of ring atoms" refers to the number of atoms constituting the ring itself of a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) in which atoms are bonded to form a ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The "number of ring atoms" described below is the same unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.
[0068] "Halogen" refers to F, Cl, Br or I.
[0069] Surface engineering and additive engineering have promoted the development of high-performance perovskite solar cells. At present, organic small molecules are often used as additives to perovskite precursor solutions or as post-treatment interface modifiers to improve the photoelectric conversion efficiency. Among them, organic small molecules mainly include propylamine, butylamine, ethylenediamine, phenylethylamine, 5-aminovaleric acid, naphthylmethylammonium iodide (NMAI) and phenylethylamine hydroiodide (PEAI). However, the high instability of organic small molecules causes them to diffuse and migrate in large quantities in the perovskite layer, which has a serious impact on the long-term stability of the battery.
[0070] External encapsulation technology uses materials such as glass and EVA to encapsulate the battery from the outside. It is currently a relatively common technology for isolating the battery from the outside world. To a certain extent, it overcomes a series of problems such as battery failure and lead leakage. However, in order to solve the problem more fundamentally from a chemical perspective, the in-situ polymerization internal encapsulation (IPIE) strategy has gradually become the focus of attention. However, some organic additives used in IPIE technology have problems such as high operating temperature and poor passivation effect on grain boundaries or interfaces, which have a certain negative impact on the efficiency and stability of perovskite solar cells. Therefore, it is urgent to develop a suitable organic additive to improve the photoelectric conversion efficiency of perovskite solar cells while improving their long-term stability in the working environment.
[0071] Based on this, in the first aspect of the present application, a perovskite crystal combination material is provided.
[0072] In some embodiments, a perovskite crystalline composite material includes a perovskite precursor and an organic additive;
[0073] The organic additive has a structure as shown in the general formula (I):
[0074] (I);
[0075] Each occurrence of R1 independently includes -H and a substituted or unsubstituted C1~C6 alkyl group;
[0076] R2 includes one of a substituted or unsubstituted C1~C6 alkylene group and a substituted or unsubstituted C1~C6 alkyleneoxy group.
[0077] The organic additive contained in the perovskite crystal combination material of the present application has two acrylic functional groups, and the lone pair of electrons of the oxygen atom in the ester group coordinates with the metal bond break (such as lead bond break) at the grain boundary or interface, and the ester group forms a hydrogen bond with the halogen bond break, thereby achieving a dual chemical passivation effect, effectively reducing the non-radiative recombination at the grain boundary or interface. The organic additive has only two cross-linking sites, and will not form a cross-linked polymer with spatial stereoscopicity, but will form a cross-linked polymer with a flexible main chain, which is conducive to reducing the system hardness of the rigid perovskite material, and well fills the grain boundaries in the perovskite film, thereby improving the filling factor of the device. At the same time, the organic additive, as a macromonomer that can undergo cross-linking polymerization, overcomes the problems of high activity, volatility and easy diffusion and migration of organic small molecules, and improves the mechanical durability of the perovskite layer. In addition, the flexible regulation of R1 and R2 in the organic additive can play the role of water and oxygen blocking and adjusting the band gap. Therefore, the perovskite solar cell prepared by the perovskite crystal combination material provided by the present application not only achieves high photoelectric conversion efficiency, but also shows excellent long-term stability.
[0078] If there are more than two cross-linking sites in the organic additive, a cross-linked polymer with a tetrahedral structure or a three-dimensional network structure will be formed. The high rigidity and spatial stereoscopic properties of this cross-linked polymer will cause it to occupy too large a position in the grain boundary of the perovskite material, blurring the grain boundary of the perovskite material and forming a new phase, which poses a greater challenge to the stability of the battery. This application controls the cross-linking sites of the organic additive to two, and at the same time regulates R1 and R2 in the organic additive, which can not only form a flexible cross-linked polymer, but also the organic additive has a small molecular weight and a low cross-linking temperature, which is within the temperature range that the perovskite material can withstand (≤150°C). At the same time, the required cross-linking time is short, which is very suitable for the preparation of high-performance perovskite solar cells.
[0079] It is understood that each occurrence of R1 independently includes one of -H and substituted or unsubstituted C1~C6 alkyl. Further optionally, each occurrence of R1 independently includes one of -H and C1~C6 alkyl, such as one of -H, C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl and C6 alkyl. Still further optionally, each occurrence of R1 independently includes one of -H and C1~C3 alkyl. Still further optionally, each occurrence of R1 independently includes one of -H and -CH3.
[0080] It is understandable that R2 includes one of a substituted or unsubstituted C1~C6 alkylene group and a substituted or unsubstituted C1~C6 alkyleneoxy group. Further optionally, R2 includes one of C1~C6 alkylene, halogen-substituted C1~C6 alkylene, amino-substituted C1~C6 alkylene and C1~C6 alkyleneoxy, such as C1 alkylene, C2 alkylene, C3 alkylene, C4 alkylene, C5 alkylene, C6 alkylene, halogen-substituted C1 alkylene, halogen-substituted C2 alkylene, halogen-substituted C3 alkylene, halogen-substituted C4 alkylene, halogen-substituted C5 alkylene, halogen-substituted C6 alkylene, amino-substituted C1 alkylene, amino-substituted C2 alkylene, amino-substituted C3 alkylene, amino-substituted C4 alkylene, amino-substituted C5 alkylene, amino-substituted C6 alkylene, C1 alkyleneoxy, C2 alkyleneoxy, C3 alkyleneoxy, C4 alkyleneoxy, C5 alkyleneoxy and C6 alkyleneoxy. Still further optionally, R2 includes one of C2~C4 alkylene, halogen-substituted C4~C6 alkylene, amino-substituted C4~C6 alkylene and C2~C4 alkyleneoxy.
[0081] Further optionally, R2 includes -CH2CH2-, -CH2OCH2-, -CH2(CF2)4CH2- and In one of the above, * indicates a connection site.
[0082] Optionally, the organic additive has one of the structures shown in general formulas (II) to (V):
[0083] (II);
[0084] (III);
[0085] (IV);
[0086] (V).
[0087] Among them, the organic additive shown in formula (II) is ethylene glycol dimethacrylate (EDGMA); the organic additive shown in formula (III) is oxybis(methylene) bis(2-methylacrylate), and the introduction of ether bonds can provide additional lone pairs of electrons to coordinate with the lead bond break, thereby enhancing the passivation effect; the name of the organic additive shown in formula (IV) is octafluoro-1,6-hexanediol diacrylate (2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl diacrylate), and the introduction of fluorine elements enhances the hydrophobicity of the organic additive, thereby reducing water vapor corrosion; the name of the organic additive shown in formula (V) is 2-aminopentane-2,3-diyl bis(2-methylacrylate), and the amino group (-NH2) can form hydrogen bonds with halogens, which is conducive to promoting the coordination of the ester group to the lead bond break under a suitable configuration, thereby improving the efficiency and stability of the perovskite.
[0088] It can be understood that in the perovskite crystal combination material, the perovskite precursor and the organic additive are blended; or, the perovskite precursor and the organic additive are independent of each other; or, the perovskite precursor and part of the organic additive are blended, and the remaining organic additive and the perovskite precursor are independent of each other. That is, the perovskite precursor and the organic additive can be mixed and packaged together, or they can be packaged separately, and blended and applied when used or applied separately when used.
[0089] Optionally, the molar ratio of the perovskite precursor to the organic additive is 1:(0.005~0.3), for example, 1:0.005, 1:0.008, 1:0.01, 1:0.02, 1:0.05, 1:0.08, 1:0.1, 1:0.12, 1:0.15, 1:0.18, 1:0.2, 1:0.22, 1:0.25 and 1:0.3, and can be further optionally 1:(0.01~0.1).
[0090] Optionally, the perovskite crystalline composite material further includes a perovskite additive and an organic solvent.
[0091] Optionally, the chemical formula of the perovskite precursor is ABX3, wherein the A ions include FA + 、MA + , Cs + , Rb + and K + One or more of the B ions include Pb 2+ Sn 2+ and Ge 2+One or more of the X ions include Cl - Br - ,I - , CN - and SCN - Further optionally, the chemical formula of the perovskite precursor includes MAPbI3, FAPbI3, CsPbI3 and FA x MA y Cs z One of PbI3, where x+y+z=1, and 0 <x<1,0<y<1,0<z<1。
[0092] Optionally, the perovskite additive includes one or more of MACl, PbCl2, MABr, FAI and halogen ammonium salts; wherein the halogen ammonium salt includes one or more of NH4Cl, NH4Br and NH4I. Further optionally, the perovskite additive includes MACl and PbCl2.
[0093] Optionally, the molar ratio of the perovskite precursor to the perovskite additive is 1:(0.005~0.3), for example, 1:0.005, 1:0.008, 1:0.01, 1:0.02, 1:0.05, 1:0.08, 1:0.1, 1:0.12, 1:0.15, 1:0.18, 1:0.2, 1:0.22, 1:0.25 and 1:0.3, and can further be 1:(0.01~0.1).
[0094] Understandably, the perovskite additive does not serve as a component in the perovskite precursor ABX3, but rather assists in the nucleation of perovskite, first forming a perovskite skeleton when the solvent is supersaturated, and then being replaced by the components of the perovskite precursor, playing a role in regulating the crystallization rate and improving the crystal morphology.
[0095] Optionally, the organic solvent includes one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetonitrile (MeCN), dimethyl sulfoxide (DMSO), ethanol (MeOH), isopropyl alcohol (IPA) and acetone, and may further be one or more of DMF, DMSO and IPA.
[0096] It can be understood that the organic solvent is the dispersion medium for the perovskite precursor and the organic additive. The use of a suitable organic solvent can effectively improve the film formation kinetics and film quality of the perovskite layer. The solubility of a single solvent in the perovskite precursor is low, which is not conducive to improving the density and stability of the perovskite layer. Therefore, the organic solvent for dissolving the perovskite precursor usually adopts a mixed solvent, such as DMF and DMSO, to improve the solubility of the perovskite precursor, regulate grain growth, and improve the flatness and density of the perovskite layer. In addition, if the organic additive is not blended with the perovskite precursor, a single solvent can be used to dissolve the organic additive, such as using IPA to dissolve the organic additive.
[0097] In a second aspect of the present application, a method for preparing a solar cell is provided, which is the application of the perovskite crystalline combination material as described above in the field of perovskite solar cells.
[0098] In some embodiments, a method for preparing a solar cell comprises the following steps:
[0099] S300: forming a perovskite layer on the substrate layer using a perovskite crystal combination material;
[0100] The perovskite crystalline composite material is the perovskite crystalline composite material as described above.
[0101] It can be understood that, considering that the perovskite precursor and the organic additive in the perovskite crystalline composite material can be in a state of complete blending, mutual independence and partial blending, step S300 can be divided into multiple implementations. The different implementations of step S300 are described in detail below.
[0102] In some embodiments, the perovskite precursor and the organic additive contained in the perovskite crystalline composite material are mixed, and the perovskite layer is formed on the substrate layer using the perovskite crystalline composite material, comprising the following steps:
[0103] S311: preparing a mixed solution containing a perovskite precursor and an organic additive;
[0104] S312: applying the mixed solution on the base layer to form a first liquid film;
[0105] S313: Annealing the first liquid film to prepare a perovskite layer.
[0106] It can be understood that the perovskite precursor and the organic additive contained in the perovskite crystal combination material are mixed in a mixed solution. The molar ratio of the perovskite precursor to the organic additive in the mixed solution is 1: (0.005-0.3), and can further be 1: (0.01-0.1).
[0107] Optionally, the concentration of the perovskite precursor in the mixed solution is 0.8 mol / L to 2 mol / L, for example, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L and 2 mol / L, and can further be 1.2 mol / L to 1.8 mol / L.
[0108] Optionally, the molar percentage of the organic additive in the mixed solution is 0.5 mol% to 30 mol%, and can further be 1 mol% to 10 mol%. In the present application, the molar percentage of the organic additive in the mixed solution refers to the ratio of the concentration of the organic additive in the mixed solution to the concentration of the perovskite precursor. For example, in the mixed solution, the concentration of the perovskite precursor is 1 mol / L, and the molar percentage of the organic additive is 0.5 mol% to 30 mol%, that is, the concentration of the organic additive is 0.005 mol / L to 0.3 mol / L, and so on.
[0109] Optionally, the mixed solution further includes a perovskite additive and an organic solvent; wherein the molar percentage of the perovskite additive in the mixed solution is 0.5 mol% to 30 mol%, and may further be 1 mol% to 10 mol%. The molar percentage of the perovskite additive in the mixed solution refers to the ratio of the concentration of the perovskite additive to the concentration of the perovskite precursor in the mixed solution; the specific types of the perovskite additive and the organic solvent are as described above and will not be repeated here.
[0110] Optionally, the base layer includes one of a transparent conductive layer, an electron transport layer (ETL), an electron transport layer provided with a mesoporous layer, a hole transport layer (HTL) and an interface modification layer, and can further be a hole transport layer or an interface modification layer.
[0111] Optionally, the method of coating the mixed solution on the substrate layer includes one or more of spin coating, spray coating, blade coating and slit coating, and further may be spin coating, wherein the rotation speed of the spin coating is 5000 rpm to 6000 rpm and the time is 20s to 60s.
[0112] Optionally, the temperature of annealing the first liquid film is 140° C. to 160° C., and the time is 15 min to 40 min.
[0113] It is understandable that before the annealing treatment, the organic solvent can also be removed by an anti-solvent method, a vacuum method and a flash evaporation method. Among them, the anti-solvent used in the anti-solvent method can be chlorobenzene, ethyl acetate, anisole and dimethyl ethyl carbonate, etc.
[0114] The above-mentioned embodiment forms a perovskite layer by blending a perovskite precursor and an organic additive. During the annealing process, the organic additive is synchronously annealed with the perovskite material and thermally cross-linked in situ, thereby suppressing the thermal expansion of the perovskite material during the annealing process, releasing residual stress, and improving the mechanical properties of the perovskite layer, making it more mechanically resistant during the component packaging process. The annealed perovskite layer contains a cross-linked polymer of the organic additive, which plays a role in passivating the grain boundaries and enhancing the intrinsic stability of the perovskite layer, thereby achieving high photoelectric conversion efficiency and excellent long-term stability.
[0115] In some embodiments, the perovskite precursor and the organic additive contained in the perovskite crystalline composite material are independent of each other, and forming a perovskite layer on the substrate layer using the perovskite crystalline composite material includes the following steps:
[0116] S321: preparing a first solution containing a perovskite precursor and a second solution containing an organic additive;
[0117] S322: forming adjacent perovskite layers and interface modification layers on the substrate layer using a first solution and a second solution by a solution method.
[0118] It can be understood that the perovskite precursor and the organic additive contained in the perovskite crystal combination material are independent of each other and are dissolved in the first solution and the second solution respectively. The molar ratio of the perovskite precursor in the first solution and the organic additive in the second solution is 1: (0.005-0.3), such as 1: 0.005, 1: 0.008, 1: 0.01, 1: 0.02, 1: 0.05, 1: 0.08, 1: 0.1, 1: 0.12, 1: 0.15, 1: 0.18, 1: 0.2, 1: 0.22, 1: 0.25 and 1: 0.3, and can be further selected as 1: (0.01-0.1).
[0119] Optionally, the concentration of the perovskite precursor in the first solution is 0.8 mol / L to 2 mol / L, for example, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L and 2 mol / L, and can further be 1.2 mol / L to 1.8 mol / L.
[0120] Optionally, the first solution further comprises a perovskite additive and an organic solvent; wherein the molar percentage of the perovskite additive in the first solution is 0.5 mol% to 30 mol%, and may further be 1 mol% to 10 mol%. The molar percentage of the perovskite additive in the mixed solution refers to the ratio of the concentration of the perovskite additive to the concentration of the perovskite precursor in the mixed solution; the specific types of the perovskite additive and the organic solvent are as described above and will not be described in detail herein.
[0121] Optionally, the molar percentage of the organic additive in the second solution is 0.5 mol% to 30 mol%, and may further be 1 mol% to 10 mol%. In the present application, the molar percentage of the organic additive in the second solution refers to the ratio of the concentration of the organic additive in the second solution to the concentration of the perovskite precursor in the first solution. For example, the concentration of the perovskite precursor in the first solution is 1 mol / L, and the molar percentage of the organic additive in the second solution is 0.5 mol% to 30 mol%, that is, the concentration of the organic additive in the second solution is 0.005 mol / L to 0.3 mol / L, and so on.
[0122] Optionally, forming an adjacent perovskite layer and an interface modification layer on a substrate layer using a first solution and a second solution by a solution method comprises the following steps:
[0123] Applying the first solution on the base layer to form a second liquid film;
[0124] annealing the second liquid film to form a perovskite layer;
[0125] applying the second solution on the perovskite layer to form a third liquid film;
[0126] The third liquid film is annealed to form an interface modification layer.
[0127] Among them, coating the first solution on the base layer and coating the second solution on the perovskite layer independently include one or more of spin coating, spray coating, blade coating and slit coating, and spin coating can be further selected; the rotation speed of the spin coating method is 5000rpm~6000rpm, and the time is 20s~60s; the temperature for annealing the second liquid film is 140℃~160℃, and the time is 15min~40min; the temperature for annealing the third liquid film is 120℃~150℃, and the time is 5min~15min.
[0128] The above-mentioned embodiment utilizes mutually independent perovskite precursors and organic additives to respectively form adjacent perovskite layers and interface modification layers. The organic additives are in-situ polymerized on the surface of the perovskite layer to form an interface modification layer, which can not only adjust the band structure of the perovskite layer, so that the energy level of carrier transmission is lower and non-radiative recombination is reduced, but also chemically anchor the broken bonds at the interface, thereby freezing the lattice, preventing ion escape, and resisting the penetration of harmful molecules such as water, oxygen and metal elements in the top electrode, effectively improving the long-term stability of the perovskite layer, thereby achieving high photoelectric conversion efficiency and excellent long-term stability.
[0129] In some embodiments, the perovskite precursor and the organic additive contained in the perovskite crystalline composite material are partially mixed, and the perovskite layer is formed on the substrate layer using the perovskite crystalline composite material, comprising the following steps:
[0130] S331: preparing a third solution containing a perovskite precursor and a portion of an organic additive, and a fourth solution containing the remaining organic additive;
[0131] S332: forming adjacent perovskite layers and interface modification layers on the substrate layer using a solution method using the third solution and the fourth solution.
[0132] It can be understood that the perovskite precursor and part of the organic additive contained in the perovskite crystal combination material are mixed in the third solution, and the remaining organic additive is dissolved in the fourth solution alone. The ratio of the molar amount of the perovskite precursor in the third solution and the total molar amount of the organic additive in the third solution and the organic additive in the fourth solution is 1: (0.005-0.3), and can further be 1: (0.01-0.1).
[0133] Optionally, the concentration of the perovskite precursor in the third solution is 0.8 mol / L to 2 mol / L, for example, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L and 2 mol / L, and can further be 1.2 mol / L to 1.8 mol / L.
[0134] Optionally, the sum of the molar percentage of the organic additive in the third solution and the molar percentage of the organic additive in the fourth solution is 0.5 mol% to 30 mol%, and can further be 1 mol% to 10 mol%. The molar percentage of the organic additive in the third solution is 1 mol% to 20 mol%, and can further be 1 mol% to 10 mol%. The molar percentage of the organic additive in the fourth solution is 1 mol% to 20 mol%, and can further be 1 mol% to 10 mol%.
[0135] Optionally, the third solution further includes a perovskite additive and an organic solvent; wherein the molar percentage of the perovskite additive in the third solution is 0.5 mol% to 30 mol%, and may further be 1 mol% to 10 mol%. The molar percentage of the perovskite additive in the mixed solution refers to the ratio of the concentration of the perovskite additive to the concentration of the perovskite precursor in the mixed solution; the specific types of the perovskite additive and the organic solvent are as described above and will not be repeated here.
[0136] Optionally, forming an adjacent perovskite layer and an interface modification layer on the substrate layer using a solution method using the third solution and the fourth solution comprises the following steps:
[0137] applying the third solution on the base layer to form a fourth liquid film;
[0138] annealing the fourth liquid film to form a perovskite layer;
[0139] applying the fourth solution on the perovskite layer to form a fifth liquid film;
[0140] The fifth liquid film is annealed to form an interface modification layer.
[0141] Among them, coating the third solution on the base layer and coating the fourth solution on the perovskite layer independently include one or more of spin coating, spray coating, blade coating and slit coating, and spin coating can be further selected; the rotation speed of the spin coating method is 5000rpm~6000rpm, and the time is 20s~60s; the temperature for annealing the fourth liquid film is 140℃~160℃, and the time is 15min~40min; the temperature for annealing the fifth liquid film is 120℃~150℃, and the time is 5min~15min.
[0142] The above-mentioned implementation method adopts an integrated in-situ polymerization inner encapsulation strategy, forms a perovskite layer by blending a perovskite precursor and an organic additive, and uses the organic additive to perform in-situ polymerization on the surface of the perovskite layer to form an interface modification layer. It has the advantages of the first two implementation methods and can simultaneously regulate the crystallization properties of the perovskite layer, passivate grain boundary defects and interface defects, and enhance mechanical properties, thereby optimizing the photoelectric conversion efficiency and enhancing long-term stability, which is conducive to the preparation of high-performance perovskite solar cells.
[0143] In a third aspect of the present application, a solar cell is provided, which is manufactured using the solar cell manufacturing method as described above.
[0144] Optionally, the solar cell includes a first carrier transport layer, a perovskite layer, a second carrier transport layer and a top electrode stacked in sequence; or, the solar cell includes a first carrier transport layer, a perovskite layer, an interface modification layer, a second carrier transport layer and a top electrode stacked in sequence.
[0145] Optionally, the first carrier transport layer is an electron transport layer (ETL), and the second carrier transport layer is a hole transport layer (HTL), that is, the solar cell has a planar formal structure.
[0146] Optionally, the first carrier transport layer is a hole transport layer (HTL), and the second carrier transport layer is an electron transport layer (ETL), that is, the solar cell has a planar inverted structure.
[0147] Optionally, the perovskite layer has a thickness of 200 nm to 1000 nm, for example, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm and 1000 nm.
[0148] Optionally, the thickness of the interface modification layer is 10 nm to 200 nm, for example, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm and 200 nm.
[0149] Optionally, the solar cell further comprises an interface modification layer disposed between the first carrier transport layer and the perovskite layer.
[0150] Optionally, the solar cell further includes a transparent conductive layer, and the first carrier transport layer is disposed on the transparent conductive layer, that is, the first carrier transport layer is disposed between the transparent conductive layer and the perovskite layer.
[0151] Optionally, the material of the transparent conductive layer is a transparent conductive oxide (TCO), such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), indium gallium tin oxide (IGTO), indium zinc tin oxide (IZTO) and indium gallium zinc tin oxide (IGZTO), and ITO may be further selected; the preparation method of the transparent conductive layer may be vacuum evaporation, magnetron sputtering, atomic layer deposition, chemical vapor deposition, ion beam deposition, pulsed laser deposition, spin coating, doctor blade coating, 3D printing, screen printing, spraying, etc., with a thickness of 30nm~200nm.
[0152] Optionally, the material of the electron transport layer includes titanium oxide, tin oxide, zinc oxide, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,7-diphenyl-1,10-phenanthroline (Bphen), fullerene (C 60 ) and one or more of fullerene derivatives, wherein the fullerene derivatives include indene-C 60 Bisadduct (ICBA), [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM) and [6,6]-phenyl-C 71 -Methyl butyrate (PC 70 BM), and may further be C 60The electron transport layer can be prepared by solution spin coating, vacuum evaporation, magnetron sputtering, atomic layer deposition, etc., with a thickness of 10nm~40nm.
[0153] Optionally, the material of the hole transport layer includes one or more of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), 4,4'-cyclohexylbis[N,N-bis(4-methylphenyl)aniline] (TAPC), 4,4'-bis(9-carbazole)biphenyl (CBP), 1,3-di-9-carbazolebenzene (mCP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), copper phthalocyanine (CuPc) and copper iodide (CuI), and 2PACz may be further selected. The hole transport layer can be prepared by solution spin coating, vacuum evaporation, magnetron sputtering, atomic layer deposition, etc., with a thickness of 10nm~100nm.
[0154] Optionally, the material of the top electrode includes one or more of gold, silver, copper, palladium, titanium, aluminum, chromium and nickel, and further silver can be selected. The top electrode can be prepared by vacuum evaporation, sputtering, atomic layer deposition, 3D printing, screen printing, inkjet printing, etc., with a thickness of 0.1 μm to 10 μm.
[0155] In a third aspect of the present application, a stacked cell is provided, comprising a silicon cell, a composite layer and a top cell stacked in sequence, and the top cell is the solar cell as described above.
[0156] Optionally, the silicon cell is an N-type crystalline silicon solar cell with a tunnel oxide passivated contact (TOPCon) structure, wherein the silicon cell comprises a bottom electrode, a silicon nitride layer, a p-type doped polysilicon layer, a first tunnel oxide layer, an n-type single crystal silicon layer, a second tunnel oxide layer and an n-type doped polysilicon layer stacked in sequence, and the composite layer is located on the n-type doped polysilicon layer.
[0157] Optionally, the solar cell includes a hole transport layer, a perovskite layer, an electron transport layer and a top electrode stacked in sequence, or the solar cell includes a hole transport layer, a perovskite layer, an interface modification layer, an electron transport layer and a top electrode stacked in sequence, and the hole transport layer is located above the composite layer.
[0158] Optionally, the solar cell further comprises an interface modification layer disposed between the hole transport layer and the perovskite layer, wherein the interface modification layer is prepared using the organic additives described above.
[0159] Optionally, the solar cell further includes a buffer layer disposed between the electron transport layer and the top electrode. The buffer layer can reduce the loss of the perovskite cell when preparing the top electrode, and its raw materials can be selected from one or more of tin oxide (SnO2), molybdenum oxide (MoO3), and 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP). The preparation method can be atomic layer deposition, vacuum thermal evaporation or solution spin coating, etc., and the thickness is 5nm~100nm.
[0160] In a fourth aspect of the present application, a photovoltaic module is provided, comprising a first packaging panel, a first packaging film, a battery string, a second packaging film and a second packaging panel stacked in sequence, and the battery string is formed by electrically connecting a plurality of solar cells as described above, or by electrically connecting a plurality of stacked batteries as described above.
[0161] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0162] Example 1
[0163] See also Figure 1 , which is a schematic diagram of the structure of the solar cell of this embodiment. Figure 1 It can be seen that the solar cell of this embodiment includes a transparent conductive layer 11, a hole transport layer 12, a perovskite layer 13, an electron transport layer 14 and a top electrode 15 which are stacked in sequence. The method for preparing the solar cell is as follows:
[0164] (1) Pretreatment of the transparent conductive layer 11: Using ITO glass as the transparent conductive layer 11, the transparent conductive layer 11 was ultrasonically cleaned for 20 min using a detergent, deionized water, ethanol, and acetone in sequence; nitrogen was blown in to dry the surface of the transparent conductive layer 11, and the layer was sent to a UV-ozone cleaner for treatment for 20 min to remove residual organic matter on the surface and improve surface wettability.
[0165] (2) Preparation of the hole transport layer 12: In a glove box filled with N2, 2PACz was dissolved in IPA to prepare a 2PACz solution with a concentration of 0.5 mg / mL, and filtered using a filter with a pore size of 0.22 μm; the 2PACz solution was spin-coated onto the pretreated transparent conductive layer 11, accelerated from 5000 rpm to 6000 rpm at an acceleration of 3000 rpm / s, and then spin-coated at a constant speed for 30 s; the solution was annealed on a hot plate at 100°C for 5 min to allow the 2PACz to form a self-assembled monolayer (SAM), thereby obtaining the hole transport layer 12.
[0166] (3) Preparation of perovskite layer 13:
[0167] S311: preparing a mixed solution containing a perovskite precursor and an organic additive.
[0168] According to the chemical formula of the perovskite precursor, FAI, CsI and PbI2 were weighed, dissolved in 1 mL of organic solvent, and the perovskite additive and organic additive were added to obtain a mixed solution. The chemical formula of the perovskite precursor is FA 0.9 Cs 0.1 PbI3, with a concentration of 1.4 mol / L; the perovskite additives are 5 mol% (0.07 mol / L) PbCl2 and 25 mol% (0.35 mol / L) MACl; the organic additive is ethylene glycol dimethacrylate (EDGMA), with a concentration of 0.1 mol% (0.0014 mol / L); the organic solvent is composed of DMF and DMSO with a volume ratio of 4:1.
[0169] S312: Spin-coat the mixed solution on the surface of the hole transport layer 12, accelerate from 5000 rpm to 6000 rpm at an acceleration of 1000 rpm / s, and then spin-coat at a constant speed for 50 seconds; add anti-solvent chlorobenzene in the last 10 seconds of high-speed spin coating, and after spin coating, obtain a first liquid film.
[0170] S313: Transfer the first liquid film to a hot plate at 150° C. and anneal for 15 minutes to obtain a perovskite layer 13 .
[0171] (4) Preparation of the electron transport layer 14 and the top electrode 15: 20 nm thick C 60 and 15 nm thick BCP to form an electron transport layer 14 ; and 150 nm thick Ag is evaporated on the surface of the electron transport layer 14 to form a top electrode 15 .
[0172] Example 2
[0173] See also Figure 2 , which is a schematic diagram of the structure of the solar cell of this embodiment. Figure 2It can be seen that the solar cell of this embodiment includes a transparent conductive layer 21, a hole transport layer 22, a perovskite layer 23, an interface modification layer 24, an electron transport layer 25 and a top electrode 26 which are stacked in sequence. The preparation method of the solar cell is as follows:
[0174] (1) Pretreatment of the transparent conductive layer 21: the same as in Example 1.
[0175] (2) Preparation of the hole transport layer 22: the same as in Example 1.
[0176] (3) Preparation of perovskite layer 23 and interface modification layer 24:
[0177] S321: preparing a first solution containing a perovskite precursor and a second solution containing an organic additive.
[0178] According to the chemical formula of the perovskite precursor, FAI, CsI and PbI2 are weighed, dissolved in 1 mL of organic solvent, and the perovskite additive is added to obtain the first solution. The chemical formula of the perovskite precursor is FA 0.9 Cs 0.1 PbI3, concentration is 1.4 mol / L; the perovskite additives are 5 mol% (0.07 mol / L) PbCl2 and 25 mol% (0.35 mol / L) MACl; the organic solvent of the first solution is composed of DMF and DMSO in a volume ratio of 4:1.
[0179] The organic additive EDGMA was dissolved in the organic solvent IPA to obtain a second solution with a concentration of 1 mol% (0.014 mol / L), and the volume ratio of the perovskite precursor solution to the EDGMA solution was maintained at 1:0.5.
[0180] S322 : forming an adjacent perovskite layer 23 and an interface modification layer 24 on the hole transport layer 22 using a solution method using a first solution and a second solution.
[0181] The first solution was spin-coated on the surface of the hole transport layer 22, and the solution was accelerated from 5000 rpm to 6000 rpm at an acceleration of 1000 rpm / s, and then spin-coated at a constant speed for 50 seconds. Anti-solvent chlorobenzene was added dropwise in the last 10 seconds of high-speed spin coating. After the spin coating was completed, the solution was transferred to a hot plate at 150° C. for annealing for 15 minutes to obtain a perovskite layer 23.
[0182] The second solution was spin-coated on the surface of the perovskite layer 23 , accelerated from 5000 rpm to 6000 rpm at an acceleration of 3000 rpm / s, and then spin-coated at a constant speed for 30 seconds; and annealed on a hot plate at 150° C. for 10 minutes to obtain an interface modification layer 24 .
[0183] (4) Preparation of the electron transport layer 25 and the top electrode 26: the same as in Example 1.
[0184] Example 3
[0185] See also Figure 3 , which is a schematic diagram of the structure of the solar cell of this embodiment. Figure 3 It can be seen that the solar cell of this embodiment includes a transparent conductive layer 31, a hole transport layer 32, a perovskite layer 33, an interface modification layer 34, an electron transport layer 35 and a top electrode 36 which are stacked in sequence. The preparation method of the solar cell is as follows:
[0186] (1) Pretreatment of the transparent conductive layer 31: the same as in Example 1.
[0187] (2) Preparation of the hole transport layer 32: the same as in Example 1.
[0188] (3) Preparation of perovskite layer 33 and interface modification layer 34:
[0189] S331: preparing a third solution containing a perovskite precursor and a portion of an organic additive, and a fourth solution containing the remaining organic additive;
[0190] According to the chemical formula of the perovskite precursor, FAI, CsI and PbI2 are weighed, dissolved in 1 mL of organic solvent, and the perovskite additive and organic additive are added to obtain a third solution. The chemical formula of the perovskite precursor is FA 0.9 Cs 0.1 PbI3, concentration is 1.4 mol / L; the perovskite additives are 5 mol% (0.07 mol / L) PbCl2 and 25 mol% (0.35 mol / L) MACl; the organic additive is ethylene glycol dimethacrylate (EDGMA), the concentration is 0.1 mol% (0.0014 mol / L); the organic solvent of the third solution is composed of DMF and DMSO in a volume ratio of 4:1.
[0191] The organic additive EDGMA was dissolved in the organic solvent IPA to obtain a fourth solution with a concentration of 1 mol% (0.014 mol / L), and the volume ratio of the perovskite precursor and EDGMA (EDGMA in the third solution and EDGMA in the fourth solution) was maintained at 1:0.5.
[0192] S332: forming adjacent perovskite layers and interface modification layers on the substrate layer using a solution method using the third solution and the fourth solution.
[0193] The third solution was spin-coated on the surface of the hole transport layer 32, and the coating was performed at a constant speed after being accelerated from 5000 rpm to 6000 rpm at an acceleration of 1000 rpm / s, and the coating time was 50 s. Anti-solvent chlorobenzene was added dropwise in the last 10 s of high-speed spin coating. After the spin coating was completed, the solution was transferred to a hot plate at 150° C. and annealed for 15 min to obtain the perovskite layer 33.
[0194] The fourth solution was spin-coated on the surface of the perovskite layer 33 , accelerated from 5000 rpm to 6000 rpm at an acceleration of 3000 rpm / s, and then spin-coated at a constant speed for 30 seconds; and annealed on a hot plate at 150° C. for 10 minutes to obtain an interface modification layer 34 .
[0195] (4) Preparation of the electron transport layer 35: the same as in Example 1.
[0196] (5) Preparation of top electrode 36: same as in Example 1.
[0197] Embodiment 4-5
[0198] The structure and preparation method of the solar cell of Examples 4 to 5 are the same as those of Example 1, except that the concentration of the organic additive EDGMA in the mixed solution is as follows:
[0199] Example 4: The concentration of the organic additive EDGMA in the mixed solution is 5 mol% (0.07 mol / L);
[0200] Example 5: The concentration of the organic additive EDGMA in the mixed solution is 10 mol% (0.14 mol / L).
[0201] Embodiment 6-7
[0202] The structure and preparation method of the solar cell of Examples 6 to 7 and the examples 2 The difference lies in the concentration of the organic additive EDGMA in the first solution, which is as follows:
[0203] Example 6: The concentration of the organic additive EDGMA in the first solution is 5 mol% (0.07 mol / L);
[0204] Example 7: The concentration of the organic additive EDGMA in the first solution is 10 mol % (0.14 mol / L).
[0205] Embodiments 8 to 12
[0206] The structures and preparation methods of the solar cells of Examples 8 to 12 are the same as those of Example 3, except that the concentration of the organic additive EDGMA in the third solution or the fourth solution is as follows:
[0207] Example 8: The concentration of the organic additive EDGMA in the fourth solution is 0.1 mol% (0.0014 mol / L);
[0208] Example 9: The concentration of the organic additive EDGMA in the fourth solution is 0.2 mol% (0.0028 mol / L);
[0209] Example 10: The concentration of the organic additive EDGMA in the fourth solution is 0.8 mol% (0.0112 mol / L);
[0210] Example 11: The concentration of the organic additive EDGMA in the third solution is 0.2 mol% (0.0028 mol / L);
[0211] Example 12: The concentration of the organic additive EDGMA in the third solution is 0.4 mol % (0.0056 mol / L).
[0212] Embodiment 13
[0213] The structure and preparation method of the solar cell of this embodiment are the same as those of embodiment 3, except that the chemical formula of the perovskite precursor is FA 0.85 MA 0.05 Cs 0.1 The concentration of PbI3 and the organic additive EDGMA in the third solution is 0.4 mol% (0.0056 mol / L).
[0214] The preparation method of the third solution is as follows: FAI, MAI, CsBr and PbI2 are weighed according to the chemical formula of the perovskite precursor, dissolved in 1 mL of an organic solvent, and a perovskite additive and an organic additive are added to obtain the third solution.
[0215] Embodiment 14
[0216] The structure and preparation method of the solar cell of this embodiment are the same as those of Embodiment 3, except that the organic additive EDGMA in the third solution and the organic additive EDGMA in the fourth solution are replaced by an organic additive having a structure shown in the general formula (III):
[0217] (III).
[0218] Embodiment 15
[0219] The structure and preparation method of the solar cell of this embodiment are the same as those of embodiment 3, except that the organic additive EDGMA in the third solution and the organic additive EDGMA in the fourth solution are replaced by an organic additive having a structure shown in general formula (IV):
[0220] (IV).
[0221] Example 16
[0222] The structure and preparation method of the solar cell of this embodiment are the same as those of embodiment 3, except that the organic additive EDGMA in the third solution and the organic additive EDGMA in the fourth solution are replaced by an organic additive having a structure shown in general formula (IV):
[0223] (V).
[0224] Comparative Example 1
[0225] See also Figure 4 , which is a schematic diagram of the structure of the solar cell of this comparative example. Figure 4 It can be seen that the solar cell of this comparative example includes a transparent conductive layer 41, a hole transport layer 42, a perovskite layer 43, an electron transport layer 44 and a top electrode 45 which are stacked in sequence. The preparation method of the solar cell is as follows:
[0226] (1) Pretreatment of the transparent conductive layer 41: the same as in Example 1.
[0227] (2) Preparation of the hole transport layer 42: the same as in Example 1.
[0228] (3) Preparation of perovskite layer 43:
[0229] According to the chemical formula of the perovskite precursor, FAI, CsI and PbI2 were weighed, dissolved in 1 mL of organic solvent, and the perovskite additive was added to obtain the perovskite precursor solution. The chemical formula of the perovskite precursor is FA 0.9 Cs 0.1 PbI3, concentration is 1.4 mol / L; the perovskite additives are 5 mol% (0.07 mol / L) PbCl2 and 25 mol% (0.35 mol / L) MACl; the organic solvent of the perovskite precursor solution is composed of DMF and DMSO in a volume ratio of 4:1.
[0230] The perovskite precursor liquid was spin-coated on the surface of the hole transport layer 42, accelerated from 5000 rpm to 6000 rpm at an acceleration of 1000 rpm / s, and then uniformly spin-coated for 50 s; anti-solvent chlorobenzene was added dropwise in the last 10 s of high-speed spin coating, and after spin coating was completed, the perovskite layer 43 was obtained by transferring the liquid to a hot plate at 150°C for annealing for 15 min.
[0231] (4) Preparation of the electron transport layer 44 and the top electrode 45: the same as in Example 1.
[0232] Comparative Example 2
[0233] The organic additive was replaced by the small organic molecule 1,3-propylenediamine (NH2CH2CH2CH2NH2).
[0234] Comparative Example 3
[0235] The organic additive was replaced with trimethylolpropane triacrylate (TMTA).
[0236] Test Case
[0237] (1) MPPT stability test: MPPT is Maximum Power Point Tracker, which is used to ensure that the solar cell outputs electrical energy at the maximum efficiency. The solar cells prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were subjected to MPPT stability tests for 250 hours under illumination conditions. The results are shown in Tables 1 and Figure 5 .in, Figure 5 This is a graph showing the MPPT stability test results of the solar cell of Example 3.
[0238] Depend on Figure 5 It can be seen that the T90 life (the photoelectric conversion efficiency PCE drops to 90% of its initial efficiency) of the solar cell of Example 3 is greater than 200 hours. As shown in Table 1, the T90 life of the solar cells of Examples 1 to 16 is greater than 120 hours. Compared with Examples 1 to 16, the T90 life of the solar cells of Comparative Examples 1 to 3 is greatly reduced, only greater than 90 hours to 100 hours.
[0239] (2) Long-term stability test: The PCE of the solar cells of Examples 1 to 3 and Comparative Example 1 after being placed under different conditions for a period of time was tested, and the PCE was normalized with the newly prepared solar cell as a reference. The results are shown in Figure 6 .
[0240] Depend on Figure 6It can be seen that after the solar cell was placed in the glove box for 3 days, the PCE of Examples 1 to 3 remained above 99% of the initial efficiency, while the PCE of Comparative Example 1 dropped to below 97% of the initial efficiency. After the solar cell was placed in the glove box for 8 days, or at 120°C for 19 hours, the PCE of Examples 1 to 3 remained between 95% and 99% of the initial efficiency. After the solar cell was placed at 100°C for 68 hours and in the glove box for 13 days, the PCE of Examples 1 to 3 remained above 90% of the initial efficiency, while the PCE of Comparative Example 1 dropped to about 86% of the initial efficiency. It can be seen that the long-term stability of Examples 1 to 3 is better.
[0241] (3) Photovoltaic IV test: The photovoltaic IV test of the solar cell was carried out using the rapid scanning method, and the electrical performance of the solar cell was measured and the JV curve of the solar cell was drawn. The results are shown in Table 1 and Figure 7~Figure 9 Among them, V oc represents the open circuit voltage, J sc represents current density, FF represents fill factor, and PCE represents photoelectric conversion efficiency. Figure 7 JV curves of solar cells of Examples 1, 4 and 5; Figure 8 JV curves of solar cells of Examples 2, 6 and 7; Fig. 9 The JV curves of the solar cells of Examples 3, 8 and 9 are shown.
[0242] In embodiments 1, 4 and 5, a mixed solution is obtained by blending a perovskite precursor and an organic additive to prepare a perovskite layer with grain boundary passivation. Figure 7 As shown in Table 1, as the concentration of the organic additive EDGMA in the mixed solution increases, the electrical performance of the solar cell gradually decreases. The concentration of the organic additive in Example 1 is 0.1 mol% (0.0014 mol / L), which not only achieves a PCE of 24.71%, but also a T90 life of more than 250 h, with excellent long-term stability.
[0243] In embodiments 2, 6 and 7, an organic additive is used to form an interface modification layer on a perovskite layer without grain boundary passivation. Figure 8 As shown in Table 1, as the concentration of the organic additive in the first solution increases, the T90 life of the battery gradually decreases, and the PCE of Example 2 is the highest, reaching 24.01%.
[0244] Examples 3, 8 to 12 are to prepare the grain boundary passivation perovskite layer and the interface modification layer in sequence. Fig. 9As shown in Table 1, the concentrations of the organic additives in the third solution and the fourth solution are different, and have different effects on the electrical properties and stability of the solar cell. Among them, the T90 life of Example 10 is the highest, reaching more than 220 hours; and the PCE of Example 12 is the highest, reaching 24.12%.
[0245] Compared with Example 12, Example 13 changed the perovskite precursor, and the PCE was slightly reduced, but the T90 lifespan remained the same. Compared with Example 3, Examples 14 to 16 changed the composition of the organic additive, and the PCE and T90 lifespan of Examples 14 to 15 were reduced, while the PCE of Example 16 was slightly improved.
[0246] Compared with Examples 1 to 16, Comparative Example 1 did not use organic additives to passivate the grain boundaries of the perovskite layer or form an interface modification layer on the perovskite layer, and the electrical properties and long-term stability were significantly deteriorated. Comparative Example 2 used traditional organic small molecules instead of the organic additives of the present application, and Comparative Example 3 used TMTA with multiple cross-linking sites instead of the organic additives of the present application, which both resulted in a significant reduction in electrical properties and long-term stability.
[0247] In summary, the use of the perovskite crystal combination material provided in the present application, whether used to prepare a perovskite layer with grain boundary passivation or to prepare an interface modification layer on the perovskite layer, can enable perovskite solar cells to have both high photoelectric conversion efficiency and excellent long-term stability.
[0248] Table 1. Comparison of electrical properties of solar cells
[0249]
[0250] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0251] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A perovskite crystal composite material, characterized in that: including perovskite precursors and organic additives; The organic additive has a structure as shown in the general formula (I): (Ⅰ); Each occurrence of R1 independently includes -H and a substituted or unsubstituted C1~C6 alkyl group; R2 includes one of a substituted or unsubstituted C1~C6 alkylene group and a substituted or unsubstituted C1~C6 alkyleneoxy group.
2. The perovskite crystal composite material according to claim 1, characterized in that: Each occurrence of R1 independently includes one of -H and C1~C3 alkyl; R2 includes one of C2~C4 alkylene, halogen-substituted C4~C6 alkylene, amino-substituted C4~C6 alkylene and C2~C4 alkyleneoxy.
3. The perovskite crystal composite material according to claim 2, characterized in that: Each occurrence of R1 independently includes one of -H and -CH3; R2 includes -CH2CH2-, -CH2OCH2-, -CH2(CF2)4CH2- and In one of the above, * indicates a connection site.
4. The perovskite crystal composite material according to any one of claims 1 to 3, characterized in that: The molar ratio of the perovskite precursor to the organic additive is 1:(0.005-0.3).
5. The perovskite crystal composite material according to claim 4, characterized in that: The perovskite crystalline composite material further includes a perovskite additive and an organic solvent.
6. The perovskite crystal composite material according to claim 5, characterized in that: The perovskite crystalline composite material satisfies one or more of the following conditions: (1) The chemical formula of the perovskite precursor is ABX3, wherein the A ions include FA + 、MA + , Cs + , Rb + and K + One or more of the B ions include Pb 2+ Sn 2+ and Ge 2+ One or more of the X ions include Cl - Br - ,I - , CN - and SCN - One or more of; (2) The perovskite additive includes one or more of MACl, PbCl2, MABr, FAI and halogen ammonium salt; (3) The molar ratio of the perovskite precursor to the perovskite additive is 1:(0.005-0.3); (4) The organic solvent includes one or more of N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, dimethyl sulfoxide, ethanol, isopropanol and acetone.
7. A method for preparing a solar cell, characterized in that: The following steps are involved: forming a perovskite layer on a substrate layer using a perovskite crystal combination material; The perovskite crystalline composite material is the perovskite crystalline composite material according to any one of claims 1 to 6.
8. The method for preparing a solar cell according to claim 7, characterized in that: The perovskite precursor and the organic additive contained in the perovskite crystal combination material are mixed, and the perovskite crystal combination material is used to form a perovskite layer on the substrate layer, comprising the following steps: preparing a mixed solution containing the perovskite precursor and the organic additive; Applying the mixed solution on the base layer to form a first liquid film; The first liquid film is annealed to prepare the perovskite layer.
9. The method for preparing a solar cell according to claim 7, characterized in that: The perovskite precursor and the organic additive contained in the perovskite crystal combination material are independent of each other. The perovskite layer is formed on the substrate layer using the perovskite crystal combination material, comprising the following steps: preparing a first solution containing the perovskite precursor and a second solution containing the organic additive; The first solution and the second solution are used to form adjacent perovskite layers and interface modification layers on the substrate layer using a solution method.
10. The method for preparing a solar cell according to claim 7, characterized in that: The method of forming a perovskite layer on a substrate layer using a perovskite crystal combination material comprises the following steps: preparing a third solution containing the perovskite precursor and a portion of the organic additive, and a fourth solution containing the remaining organic additive; The third solution and the fourth solution are used to form adjacent perovskite layers and interface modification layers on the substrate layer using a solution method.
11. A solar cell, characterized in that: The solar cell is prepared by the method for preparing the solar cell according to any one of claims 7 to 10.
12. The solar cell according to claim 11, wherein: The solar cell comprises a first carrier transport layer, a perovskite layer, a second carrier transport layer and a top electrode which are stacked in sequence; or, The solar cell comprises a first carrier transport layer, a perovskite layer, an interface modification layer, a second carrier transport layer and a top electrode which are stacked in sequence.
13. A laminated battery, characterized in that: It comprises a silicon cell, a composite layer and a top cell which are stacked in sequence, and the top cell is the solar cell as claimed in claim 11 or 12.
14. A photovoltaic module, characterized in that: It comprises a first packaging panel, a first packaging film, a battery string, a second packaging film and a second packaging panel which are stacked in sequence, and the battery string is formed by electrically connecting a plurality of solar cells as described in claim 11 or 12, or by electrically connecting a plurality of stacked batteries as described in claim 13.
Citation Information
Cited By
Anti-solvent-resistant trans-perovskite solar cell and preparation method thereof
CN119630253A
Method for buried interface passivation of perovskite thin film, and solar cell
WO2026199793A1